PEER ASSESSMENT EFFECT ON STUDENTS’ WRITING PERFORMANCE - Rulik Setiani (Edukasi Lingua Sastra, 2021)
The aim of this study is to investigate peer assessment effect on students’ writing performance. Writing is one of activities that students should be learnt to achieve language ability especially in English, but the fact they often face difficulties when they write because they have to be able in organization, content, grammar, vocabulary, and mechanics, so it is important for them needs interaction and collaboration from their friends or peers to solve those difficulties together, it called as peer assessment. Peer assessment is a common activity used in writing classroom and it can increase students’ writing performance, it also can be beneficial for both writer and teacher. For the teacher, it helps him saving time in checking students’ works, further for students, peer assessment can assist and gain their performance quantitatively and/or qualitatively by stimulating the peers to discuss, reflect, and collaborate well. Peer assessment is very effective and to be more active and productive by interacting each other students and intended communication relates the error of poor organization, misuse of punctuation, the use of faulty sentences, inappropriate the diction and capitalization. It presents the students improvement of the writing performance.